Pendampingan Penambahan Media Pembayaran QRIS Pada UMKM Toko Pertanian dan Toko Kelontong di Kabupaten Sleman - Aditya Kurnia Rizki; Wulandari, Ika (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2023)
This activity aims to assist the addition of QRIS payment channel of Toko Pertanian "Griya Tani" and Toko Kelontong "Bu Tini". Both partners are located in Mororejo, Tempel, Sleman, DIY. In their business, both partners have the same obstacles related to difficulties in finding change so that it can hamper transaction activities. Based on these problems, it is important to assistance in adding other payment channel through QRIS which can be a solution so that it will facilitate their buying and selling transaction activities. The method used is socialization by providing an understanding of QRIS and its benefits, guidance on registering and how to get a business DANA account to take QR codes as payment codes. The result of this mentoring activity is that both partners understand about QRIS and its uses and both partners have a new payment channel, namely QRIS as an alternative payment other than using cash.